2019
DOI: 10.1111/1467-8551.12327
|View full text |Cite
|
Sign up to set email alerts
|

Governance Considerations for Seeker–Solver Relationships: A Knowledge‐Based Perspective in Crowdsourcing for Innovation Contests

Abstract: The need to solve innovation problems and insource knowledge has led to an increasing number of organizations engaging in crowdsourcing activities and subsequently establishing working relationships with winning solution providers. Using a knowledge-based view and the problem-solving perspective, we develop a theoretical framework suggesting how specific innovation problem attributes (i.e. the decomposability, formulation and search space of the problem) influence the governance decision (unilateral vs. bilate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 92 publications
0
22
0
Order By: Relevance
“…Fifth, even though we cover a wide range of important types of external partners (i.e., users, suppliers, competitors, universities, entrepreneurs, and start-ups), future studies could complement our findings by considering other types of external partners. In particular, non-users and the unknown crowd can be a rich source of information for generating new ideas and project solutions [64][65][66][67][68][69][70][71]. In particular, studying the unknown crowd would be important to understand how crowdsourcing is related to external partner choice.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Fifth, even though we cover a wide range of important types of external partners (i.e., users, suppliers, competitors, universities, entrepreneurs, and start-ups), future studies could complement our findings by considering other types of external partners. In particular, non-users and the unknown crowd can be a rich source of information for generating new ideas and project solutions [64][65][66][67][68][69][70][71]. In particular, studying the unknown crowd would be important to understand how crowdsourcing is related to external partner choice.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Crowdsourcing is an increasingly adopted OI practice and has attracted growing academic interest over the past few years [24,31,[50][51][52][53][54]. Thanks to advancements in information technology, it has become easier for companies to reach dispersed individuals and leverage crowd wisdom [10,[55][56][57][58][59].…”
Section: Background and Hypothesesmentioning
confidence: 99%
“…Capaldo et al [36] think there are two kinds of knowledge distance, technological distance and geographical distance, which have opposite effect on value contribution. Piazza et al [12] found that knowledge distances between initiators and solvers tend to act as complements in specific governance structure decisions. Galati et al [37] developed an innovative model for knowledge transfer, including key factors like partners' knowledge similarities, etc.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In particular, in terms of evaluating the importance of crowdsourcing for organizational learning, it is considered to be a "new, exciting direction of research" [9][10][11]. Nowadays, in order to improve organizations' innovation abilities, some scholars [12][13][14] started to investigate the knowledge flow process in scientific crowdsourcing. Crowdsourcing, from the relationship between the initiator and the solver, is only a process of issuing tasks and completing tasks, and this is essentially a process of knowledge flow.…”
Section: Introductionmentioning
confidence: 99%